1996
DOI: 10.1016/0169-7722(95)00107-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of a diesel fuel contaminated aquifer: simulation studies in laboratory aquifer columns

Abstract: The in situ bioremediation of aquifers contaminated with petroleum hydrocarbons is commonly based on the infiltration of groundwater supplemented with oxidants (e.g., 0 2 , N0 3 ) and nutrients (e.g., NH1, Pol-). These additions stimulate the microbial activity in the aquifer and several field studies describing the resulting processes have been published. However, due to the heterogeneity of the subsurface and due to the limited number of observation wells usually available, these field data do not offer a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Six weeks after initiation of the incubation, soil of each of the four treatments was divided into 800-g (fresh weight) portions (n ϭ 15 each 3Ϫ , and Cl Ϫ ) were determined in pore water of soil samples collected (i) at the beginning of the study, (ii) after 2 weeks of incubation without plants, (iii) at planting time 6 weeks after initiation of the experiment, and (iv) at the end of the plant growth experiment, by ion chromatography (Dionex DX-100 ion chromatograph equipped with an IonPac AS4A-SC column; Dionex, Sunnyvale, Calif.) (21). Pore water was obtained as described by Nickel et al (36).…”
mentioning
confidence: 99%
“…Six weeks after initiation of the incubation, soil of each of the four treatments was divided into 800-g (fresh weight) portions (n ϭ 15 each 3Ϫ , and Cl Ϫ ) were determined in pore water of soil samples collected (i) at the beginning of the study, (ii) after 2 weeks of incubation without plants, (iii) at planting time 6 weeks after initiation of the experiment, and (iv) at the end of the plant growth experiment, by ion chromatography (Dionex DX-100 ion chromatograph equipped with an IonPac AS4A-SC column; Dionex, Sunnyvale, Calif.) (21). Pore water was obtained as described by Nickel et al (36).…”
mentioning
confidence: 99%
“…During engineered in situ bioremediation, groundwater was extracted at S2 (May 1989-April 1991) or KB12 (May 1991-February 1994, respectively, supplemented with oxidants and nutrients and reinjected in S3. laboratory aquifer columns (Hess et al, 1996;Hunkeler et al, 1998), microcosms Bregnard et al, 1997) and enrichment cultures (Häner et al, 1995 showed that microorganisms from the contaminated aquifer were able to mineralize PHC under various redox conditions. Groundwater was pumped out of well S2 (May 1989-April 1991 or well KB12 (May 1991-February 1994and October 1994-May 1995 at a rate of 72-115 m 3 day À1 .…”
Section: Site Descriptionmentioning
confidence: 99%
“…The processes in this aquifer were simulated in two independent Ž . laboratory aquifer column studies under aerobicrdenitrifying Hess et al, 1996 and Ž . anaerobic conditions Hunkeler et al, 1998 .…”
Section: Ymentioning
confidence: 99%
“…were postulated Table 3 . The scheme of processes had been successfully applied for Ž mass balances in laboratory aquifer columns and microcosms Bregnard et al, 1996;. Hess et al, 1996;Hunkeler et al, 1998 .…”
Section: Predominant Microbial and Geochemical Processes In The Sourcmentioning
confidence: 99%